ІДЕНТИФІКАЦІЯ МОДЕЛІ ЕЛЕКТРОЕНЕРГЕТИЧНОЇ СИСТЕМИ НА ОСНОВІ СИНХРОНІЗОВАНИХ ВИМІРІВ РЕЖИМНИХ ПАРАМЕТРІВ ПІД ЧАС ПЕРЕХІДНИХ ПРОЦЕСІВ - Яндульський, О.С.; Нестерко , А.Б. (Інститут електродинаміки НАН України, Київ, 2015)
Using the wide area measurement system (WAMS) for electric power system (EPS) mode parameters registration and further EPS dynamic characteristics identification can significantly improve the effectiveness of measures to preserve the stability of the power system. Effective means of the EPS mathematical model obtaining is to identify it according to the recorded transients. The complexity of active experiments and stochastic nature of EPS determine the relevance of the use of methods of identification systems, which are able to identify the deterministic model of the EPS robustly, during passive experiment. This paper investigates the features of identification and analysis of power system model for optimal control during transient frequency change. References 8, figures 2.